INDIAN MATERIALS SCIENCE RESEARCH SCIENTOMETRICS - Kumari Reena (International Journal of Multidisciplinary Research and Studies, 2021)
Another definition was provided by the Committee on Materials Science and Engineering of the National Research Council in its report titled "Materials Science and Engineering for the 1990s: Maintaining Competitiveness in the Age of Materials." This definition included performance as the fourth component of the definition. According to this report, the study of materials for the purpose of controlling the four basic elements that make up materials—properties, structure and composition, synthesis and processing, and performance—and understanding the strong interrelationships among them is what constitutes materials science. Because materials played such a crucial role in the progression of civilization, humans have maintained a close relationship with them over the millennia. During the Stone Age, which is considered to be the beginning of human life on Earth, humans exclusively used natural materials such as stone, clay, skins, and wood. Around 3000 BC, the Bronze Age began when humanity discovered copper and learned how to make it harder by alloying it with other metals.